The effects of art therapy on quality of life and psychosomatic symptoms in adults with cancer: a systematic review and meta-analysis - ShiShuang Zhou; MeiHong Yu; Zhan Zhou; LiWen Wang; WeiWei Liu; Qin Dai (BMC, 2023)
Abstract Background Cancer-related psychological and physical disorders can mean stressful and painful experiences for patients. Art therapy, a form of complementary and alternative medicine, is an increasingly popular way to decrease emotional stress, alleviate somatic symptoms, and improve quality of life in patients with cancer. However, current systematic reviews have not explored the beneficial effects of art therapy. Moreover, there have been inconsistent findings on the effect of this therapy, and there is insufficient evidence to confirm the effects in adults with cancer. The objective of this study was to determine the efficacy of art therapy in improving quality of life and psychosomatic symptoms in adults with cancer. Methods This systematic review and meta-analysis included adults with all kinds of cancer. Six English-language and three large Chinese-language databases were comprehensively searched for relevant studies. Gray literature and references were also checked. The quality of the included studies was evaluated using the Cochrane risk-of-bias assessment tool. Results Eight eligible randomized controlled trials conducted in four countries were included. Art therapy improved overall quality of life, but had no significant effect on psychological health or physical health sub-dimensions in women with cancer. Moreover, art therapy alleviated anxiety and depression, but had only a tendency toward an effect on somatic symptoms. Conclusions Moderate-quality evidence shows that art therapy is beneficial for women with cancer in terms of improving the overall quality of life and alleviating emotional symptoms (anxiety and depression). However, more high-quality randomized controlled trials are needed to determine the efficacy of this therapy on somatic symptoms.